2015
DOI: 10.1177/0743558415569731
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy and Help-Giving Responses in Irish Adolescents

Abstract: This study assessed mental health literacy in Irish adolescents (N = 187), and explored participants' help-giving responses toward hypothetical depressed peers. Participants read five vignettes, each describing an adolescent experiencing a life difficulty; two of the characters met Diagnostic and Statistical Manual of Mental Disorders (4th ed., DSM-IV) criteria for depression. The majority of participants could not identify depression or potential suicidality, but felt concerned for the depressed characters' w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 37 publications
(68 reference statements)
3
35
0
Order By: Relevance
“…However, outcomes of the present study suggest that there may be a different pattern in help seeking attitudes among Irish youth that warrants further examination contradicting previous evidence that boys prefer to cope with depression alone . Moreover, girls possess better knowledge of specific depression related behavioural and emotional features (Byrne et al, 2015), which has been attributed to their greater social exposure to depression especially during late adolescence (Burns & Rapee, 2006). The results of the present study imply that girls have better knowledge solely on one specific manifestation of depression, that is losing interest in friends and previously enjoyed activities.…”
Section: Journal Of Education and Trainingmentioning
confidence: 53%
See 2 more Smart Citations
“…However, outcomes of the present study suggest that there may be a different pattern in help seeking attitudes among Irish youth that warrants further examination contradicting previous evidence that boys prefer to cope with depression alone . Moreover, girls possess better knowledge of specific depression related behavioural and emotional features (Byrne et al, 2015), which has been attributed to their greater social exposure to depression especially during late adolescence (Burns & Rapee, 2006). The results of the present study imply that girls have better knowledge solely on one specific manifestation of depression, that is losing interest in friends and previously enjoyed activities.…”
Section: Journal Of Education and Trainingmentioning
confidence: 53%
“…For example evidence from a nationwide survey in Irish adolescents suggested that females reported significantly higher scores on a measure of MHL compared to their male counterparts (Chambers & Murphy, 2011). Another study (Byrne, Swords, & Nixon, 2015), confirmed the pattern that females tend to report higher levels of MHL than males as well as a significantly greater ability to identify depression symptoms. The relatively high rates of depression and suicide among Irish youth compared to their counterparts from other European countries (National Educational Psychological Service, 2013) require further examination of the patterns of recorded mental health literacy levels accounted for by gender, in order to expand the existing knowledge on this field and act as a starting point for developing more tailored interventions.…”
Section: Gender Differencesmentioning
confidence: 58%
See 1 more Smart Citation
“…There is evidence to suggest that disclosure of self‐harm to a peer is associated with an increase in self‐harm in those peers (Hasking et al., ). In addition, findings from this study and others suggest that friends might not be adequately equipped to provide support for a distressed peer or to signpost to further support if required (Byrne et al., ; Freake, Barley, & Kent, ). As seeking support from adults is associated with improved coping skills (Hasking et al., ), it is important to encourage young people to seek help from adults if they have self‐harmed.…”
Section: Discussionmentioning
confidence: 67%
“…An email invitation to participate was distributed (as described above) to psychologists throughout Australia. As with other questionnaires that utilise mixed methodology to evaluate open-response questions (e.g., Byrne, Swords, and Nixon, 2015), pertinent theory was used to inform the coding of responses in conjunction with themes generated within participant responses. The survey was distributed and left active over a period of 6 months and ceased at the point all avenues for recruitment were judged to have been exhausted.…”
Section: Methodsmentioning
confidence: 99%